Achieving Sustainable Loan Growth in Banking Industry: A Case Study in PT. Bank Rakyat Indonesia (Persero) Tbk - Setiawan, Jeremia Dhany; Do, Anh Dung (The Indonesian Journal of Business Administration, 2013)
PT. Bank Rakyat Indonesia (Persero) Tbk, or commonly called BRI is the oldest and widest bank in Indonesia. Founded in 1895, BRI currently has more than 8,600 working units spread across Indonesia and has been connected in real-time online. Since the beginning, BRI has focused and committed on Micro, Small and Medium Enterprises (MSMEs) segment as the core of BRI’s business. However, currently BRI suffered a setback in SMSEs segment as its major business, especially since the last three years. In fact BRI’s loan growth in the third quarter of 2012 only amounted to 15.08% which is far below the average growth of the national commercial bank which reached 23.6%. This condition is very contradict with the conditions in several years ago in which the BRI’s loan growth is always above the average loan growth of the national banks. Currently BRI is designing a business strategy to improve coordination between business units and also to accelerate the growth of its business. This Final project is composed to examine and explore the business strategy taken by BRI as the oldest and widest bank in Indonesia in order to maintain and accelerate the business growth. Hopefully with this strategy, BRI can maintain a sustainable and healthy business growth in the middle of tight conditions of business competition. Keywords: SMSE, Sustainable Growth, Business Strategy